The structure of the lithosphere of the Black Sea by the results of 3D gravity analysis and seismic tomography - T. P. Egorova; B. S. Gobarenko; T. B. Yanovskaya; K. P. Baranova (Геофизический журнал, 2012)
3D gravity analysis and local seismic tomography have been performed to study the lithosphere structure of the Black Sea. Due to gravity analysis gravity effects of different layers and levels of the model (sea water, four layers in sediments, consolidated crust) have been distinguished and residual gravity anomalies of mantle origin have been obtained. Long-wave component of these anomalies forms the vast area of positive values with small amplitude that indicates good isostatic balance of deep structures of the Black Sea. Velocity structure of lithospheric mantle of the Black Sea (down to the depth of 85 km) was studied by local seismic tomography which used travel times of P-waves from the earthquakes occurred inside the region and recorded by a net of seismic stations around the Black Sea. Results of seismic tomography study indicate heterogeneous structure of the upper mantle of the Black Sea with dominant areas of increased velocities in the western and eastern parts of the sea. Joining of two methods - gravity analysis and seismic tomography has been carried out by calculation of gravity effect of the upper mantle heterogeneities obtained by seismic tomography. Correspondence of the sign and order of magnitude of anomalous mantle gravity field obtained by two mentioned independent methods gives us an opportunity to conclude on the presence of sufficiently rigid continental lithosphere under the Black Sea.